Correlation between visual acuity and human leukocyte antigen DRB1*04 in patients with Vogt-Koyanagi-Harada disease - Norihiko Misawa; Mizuki Tagami; Takeya Kohno; Shigeru Honda (BMC Ophthalmology, 2019)
Abstract Background The common presence of human leukocyte antigen (HLA)-DRB1*04 in Vogt-Koyanagi-Harada (VKH) disease is well known. The aim of this study was to investigate the relationship between visual prognosis and HLA-DRB1*04 alleles during systemic corticosteroid therapy in patients with VKH disease. Methods This retrospective case series included 57 eyes from 29 consecutive patients with treatment-naïve VKH disease who received systemic corticosteroid therapy. Visual acuity, sex, refractive error, central retinal thickness (CRT), central choroidal thickness (CCT), and duration from onset to treatment were measured at initial and final visits. Mean values of parameters were compared with each visit. Genotyping was performed by polymerase chain reaction amplification with sequence-specific primer. Results Linear regression showed significant differences in logMAR best-corrected visual acuity between the three groups of homozygotes, heterozygotes, and normal subjects at baseline (p < 0.01), at 3 months after treatment (p < 0.01). There was no significant differences at 6 months after treatment (p = 0.257). No significant differences were detected between the three groups in age, sex, refractive error, CRT, CCT, or duration from onset to treatment. Conclusion Alleles of HLA-DRB1*04 might affect visual prognosis and be related to early response after initiation of treatment in VKH disease.